Management for quality in high technology enterprises - Fasser, Yefim (Wiley-Interscience, 2002)
The book explains how traditional "hard" management skills must be combined with new "soft" skills, why an expanding, global market necessitates an expanding, global mindset, and why a "focus on customers" must dominate all aspects of business. Momentous external and internal changes to technology enterprises demand new management procedures. Drawing on their considerable experience as leaders in a high-technology corporation, The authors show managers how to succeed in a shifting playing field. The book is devided into five parts, comprising twenty chapters. The authors explain in a lively, accessible fashion what managers must do to cope with the global changes in technology enterprises. Middle managers and engineers in high-technology manufacturing companies, as well as all professionals interested in improving their managerial knowledge and skills, will benefit from this book